2019
DOI: 10.1093/jhered/esz023
|View full text |Cite
|
Sign up to set email alerts
|

The Heritability of Behavior: A Meta-analysis

Abstract: The contribution of genetic variation to phenotypes is a central factor in whether and how populations respond to selection. The most common approach to estimating these influences is via the calculation of heritabilities, which summarize the contribution of genetic variation to phenotypic variation. Heritabilities also indicate the relative effect of genetic variation on phenotypes versus that of environmental sources of variation. For labile traits like behavioral responses, life history traits, and physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 25 publications
7
85
4
Order By: Relevance
“…The present study contributes to expanding our knowledge on the genetic bases of behavioral traits by providing quantitative genetic estimates in aggressiveness and activity in the orb‐weaving spider N. umbratica . We found that both, aggressiveness and activity, are heritable (Tables and ) and that the heritability estimates are in line with those found in vertebrates for these traits (reviewed by Dochtermann, Schwab, Anderson Berdal, Dalos, & Royauté, ; van Oers & Sinn, ). We showed sex differences in the heritability of aggressiveness, being higher in males compared to females.…”
Section: Discussionsupporting
confidence: 87%
“…The present study contributes to expanding our knowledge on the genetic bases of behavioral traits by providing quantitative genetic estimates in aggressiveness and activity in the orb‐weaving spider N. umbratica . We found that both, aggressiveness and activity, are heritable (Tables and ) and that the heritability estimates are in line with those found in vertebrates for these traits (reviewed by Dochtermann, Schwab, Anderson Berdal, Dalos, & Royauté, ; van Oers & Sinn, ). We showed sex differences in the heritability of aggressiveness, being higher in males compared to females.…”
Section: Discussionsupporting
confidence: 87%
“…An important associated issue here is that many behaviours exhibit plasticity in response to environmental factors that change relatively slowly (compared to the lifetime of the species), creating strong temporal (Allegue et al., 2017; Mitchell, Dujon, Beckmann, & Biro, 2019) or spatial (Niemelä & Dingemanse, 2017) autocorrelations. Individuals may therefore be repeatable only because of being assessed in the same repeatable environmental conditions to which they are responding plastically (Dingemanse, Kazem, et al, 2010; Martin & Réale, 2008) and not because of any genuine among‐individual variation caused by genetics or developmental effects (Dochtermann, Schwab, Berdal, Dalos, & Royaute, 2019; Dochtermann, Schwab, & Sih, 2015; Stamps & Frankenhuis, 2016). This phenomenon is called “pseudo‐repeatability” or “pseudo‐personality” (Dingemanse & Dochtermann, 2013; Westneat, Hatch, Wetzel, & Ensminger, 2011) and has been firmly documented by meta‐analyses showing that repeatability values decrease with increasing length of inter‐test intervals (Bell et al., 2009).…”
Section: Definitions and Study Designsmentioning
confidence: 99%
“…Behavioural differences among individuals that are consistent over time and across contexts (animal personality or temperament) can be found throughout the Animal Kingdom (Gosling, 2001; Kralj-Fišer & Schuett, 2014; Weiss, 2018). Additive genetic effects contribute to variation in animal personality traits (Dochtermann, Schwab & Sih, 2015), and heritability estimates are often comparable to those reported for life-history and physiological traits (Dochtermann, Schwab, Anderson Berdal, Dalos & Royauté, 2019). This renders animal personality a potential target of both natural and sexual selection (Dingemanse & Réale, 2005; Schuett, Tregenza & Dall, 2010).…”
Section: Introductionmentioning
confidence: 91%